Substitution of fermented coffee skin in commercial feed on the growth of pigs aged 1-3 months - I Dewa Nyoman Sudita; I Gusti Agus Maha Putra Sanjaya; Ni Ketut Sri Rukmini; Stefanus Nahak (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Catur Kintamani Village is one of the village areas in Kintamani-Bangli District, besides its cool climate as an Arabica coffee producing area and has received a Geographical Indication Certificate (GIS). Several coffee processing companies have developed, one of which is UPP. Catur Paramita is a business unit of Subak Abian Kenjung Sari. The problem is that coffee skin waste has not been utilized which can disrupt the environment. One alternative solution to the problem is processing coffee husk waste through fermentation using local microorganism (LMO) probiotics from coffee husks for animal feed. The purpose of this study was to determine the extent to which the appearance response of sows given fermented coffee husk waste as a substitute for commercial feed can affect the appearance of sows in the growth phase. The method used to achieve this goal is the experimental design method and the design used in this study was a completely randomized design (CRD) with 3 treatments, namely: Po (without coffee husk waste), P1 (5% substitution of coffee husk waste), and P2 (substitution of 10% coffee husk waste). Each treatment was repeated 3 times. The results showed a significant effect (P<0.05) substitution of fermented coffee husk waste in commercial feed on the growth of pigs aged 1-3 months. The greater the number of substitutions for coffee skin waste up to 10% (P2) had a significant effect (P<0.05) with an increase in body weight of 12.76 kg compared to without substitution (Po) only 7.89 kg and substitution of coffee skin waste 5% (P1) of 10.98 kg. Still, between P1 and Po the difference was not significantly (P>0.05). It can be concluded that substituting commercial feed with fermented coffee husk waste using local microorganisms (LMO) coffee skin as much as 10% significantly improves body weight gain at 1-3 months.